Preventing & responding to campus sexual abuse - McCartan, Kieran (Sexual crime, 2024)
This chapter will examine UK University's understanding and response to campus-based sexual abuse. It will discuss the extent to which policies, practices, and safeguarding have been developed, whether they have been fully imbedded, and what impact they have had. The chapter will end with a discussion of what UK Universities still need to do to support victims, especially around reporting, recording, and what support should look like as they return to study.